2003
DOI: 10.1016/s1535-6108(03)00304-0
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of caveolin-1 function by EGF leads to the loss of E-cadherin, increased transcriptional activity of β-catenin, and enhanced tumor cell invasion

Abstract: EGF receptor (EGFR) overexpression correlates with metastasis in a variety of carcinomas, but the underlying mechanisms are poorly understood. We demonstrated that EGF disrupted cell-cell adhesion and caused epithelial-to-mesenchymal transition (EMT) in human tumor cells overexpressing EGFR, and also induced caveolin-dependent endocytosis of E-cadherin, a cell-cell adhesion protein. Chronic EGF treatment resulted in transcriptional downregulation of caveolin-1 and induction of the transcriptional repressor Sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
497
5
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(548 citation statements)
references
References 118 publications
45
497
5
1
Order By: Relevance
“…Consistent with this observation, some of these repressors have been found expressed specifically at the invasive front of human invasive hepatocellular and breast carcinoma [15,16]. The expression of these repressors seems to be highly regulated by pathways, including canonical Wnt signaling, TGF-b (see below), FGF, EGF, Stat3 and nuclear factor k-B (NFk-B) signaling [17][18][19]). Notably, Snail1 is a highly unstable protein.…”
Section: Changes In Cell-cell and Cell-matrix Adhesionmentioning
confidence: 78%
“…Consistent with this observation, some of these repressors have been found expressed specifically at the invasive front of human invasive hepatocellular and breast carcinoma [15,16]. The expression of these repressors seems to be highly regulated by pathways, including canonical Wnt signaling, TGF-b (see below), FGF, EGF, Stat3 and nuclear factor k-B (NFk-B) signaling [17][18][19]). Notably, Snail1 is a highly unstable protein.…”
Section: Changes In Cell-cell and Cell-matrix Adhesionmentioning
confidence: 78%
“…Although considerable data support a role of receptor tyrosine kinases, including EGFR, in the induction of EMT (Thiery, 2002;Conacci-Sorrell et al, 2003;Lu et al, 2003;Cavallaro and Christofori, 2004;Lo et al, 2007), there remains little consensus about which downstream pathways are necessary to mediate EGFR-induced EMT. Studies within carcinoma cell lines from disparate epithelial tissues have supplied evidence for several different signaling pathways (b-catenin-TCF/LEF-1, ERK, STAT3), as well as alternate repressors of E-cadherin transcription (Twist, Slug) involved in activation of EMT (Conacci-Sorrell et al, 2003;Lu et al, 2003;Lo et al, 2007), reflective of the fact that cancer cells can use completely distinct pathways under diverse biological contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies within carcinoma cell lines from disparate epithelial tissues have supplied evidence for several different signaling pathways (b-catenin-TCF/LEF-1, ERK, STAT3), as well as alternate repressors of E-cadherin transcription (Twist, Slug) involved in activation of EMT (Conacci-Sorrell et al, 2003;Lu et al, 2003;Lo et al, 2007), reflective of the fact that cancer cells can use completely distinct pathways under diverse biological contexts. Our work in prostate cancer cells, in addition to the study in cervical cancer cells (Lee et al, 2008), adds yet another mechanistic pathway by which carcinoma cells undergo EMT, specifically an EGF/EGFR-mediated EMT pathway through Akt inhibition of GSK3b, followed by stabilization of Snail and downregulation of E-cadherin (EGFR-Akt-GSK3b-Snail-E-cadherin-EMT).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that suppression of AP-1 activity is also involved in the inhibition of proliferation by SASP. Several studies have shown that caveolin-1 functions as an important player in Wnt-independent regulation of transcriptional activity of b-catenin (Lu et al, 2003;Lu and Hunter, 2004). Caveolin-1 recruits b-catenin to caveolae membranes for its link with E-cadherin and thus promotes cell adhesion and effectively inhibits b-catenin TCF/LEF-1 signaling (Galbiati et al, 2000;Torres et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, caveolin-1 directs the distribution of E-cadherin and increases E-cadherin expression by downregulation of transcriptional repressor snail (Volonte et al, 1999;Lu et al, 2003), and E-cadherin is required for caveolin-1-mediated reduction of b-catenin-TCF/LEF-dependent transcription (Torres et al, 2007). E-cadherin is also known to negatively regulate b-catenin-mediated cell adhesion and transcription by altering its subcellular distribution.…”
Section: Discussionmentioning
confidence: 99%